Study of cesium sorption by a Brazilian bentonite (Brazilian Journal of Radiation Sciences, 2021)
Engineered and natural barriers compose the disposal system of near surface repository to store low and intermediate level radioactive wastes. Waterproofing barriers are constituted of clays, such as the bentonite, in order to avoid or to limit the release of radionuclides to with consequences to the environment and humans. Characteristics such as high cation exchange capacity, high adsorption capacity and high sealing capacity, are taken into consideration for choosing this material. The migration of radionuclides through protection barriers can occur in a variety of ways, such as surface water infiltration, groundwater intrusion, among others. Diffusion is the process which governs the contaminant transport through soil barriers. Adsorption is one of the processes that could be considered in the diffusion mechanism, and sorption isotherms are obtained from values measured in the batch-adsorption experiments. Therefore, such experiments were carried out in order to estimate the cesium sorption by the bentonite. The quantitative analysis was performed using atomic absorption and the energy dispersive X-ray fluorescence spectrometry. With the purpose to calculate the true value of cesium sorption, a mass-balance was made considering all the steps of the batch experiment, and it was found a 6% loss in the whole process. The quantity of cesium sorbed by the bentonite was 66.7 mg.g-1. At the moment, eight additional experiments are being performed, using solutions with different cesium concentrations, leading to all the necessary data for the isotherm.
Keywords: bentonite; cesium; sorption; multiple barriers.